2006
DOI: 10.1007/s00436-006-0163-6
|View full text |Cite
|
Sign up to set email alerts
|

Serological, intradermal and live flea challenge tests in the assessment of hypersensitivity to flea antigens in cats (Felis domesticus)

Abstract: The results of intradermal testing with three commercial flea antigens and a serological test for IgE antibodies to flea antigens were compared with live flea challenge in cats. Eight control cats with no prior flea exposure had negative serological test and flea challenge results. By contrast, 17 out of 27 cats with previous flea exposure showed immediate reactivity to flea challenge; reactivity at 6, 24 and 48 h after flea exposure was noted in 12, 16 and 21 cats, respectively. Seventeen of these cats had po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Historically, several methods have been proposed for confirming the diagnosis of FAD, including intradermal injection with either whole-body flea extract or extract of flea salivary antigens; serological testing to identify IgE specific for either fleas or flea saliva; evaluation of basophil activation after challenge with flea extracts; and live flea challenge exposures. [74][75][76][77] Of these, live flea challenge most closely mimics the clinical scenario and thus would be expected to be the most "specific" method of supporting a diagnosis of FAD. However, this method requires some skill and infrastructure to be performed successfully, and a live flea challenge would not be practical or ethical in clinical practice.…”
Section: Flea Allergy Dermatitismentioning
confidence: 99%
“…Historically, several methods have been proposed for confirming the diagnosis of FAD, including intradermal injection with either whole-body flea extract or extract of flea salivary antigens; serological testing to identify IgE specific for either fleas or flea saliva; evaluation of basophil activation after challenge with flea extracts; and live flea challenge exposures. [74][75][76][77] Of these, live flea challenge most closely mimics the clinical scenario and thus would be expected to be the most "specific" method of supporting a diagnosis of FAD. However, this method requires some skill and infrastructure to be performed successfully, and a live flea challenge would not be practical or ethical in clinical practice.…”
Section: Flea Allergy Dermatitismentioning
confidence: 99%
“…Flea allergy is the most common allergy in the cat. In one study, the majority of cats reacting to a live flea challenge also showed an immediate hypersensitivity on intradermal testing with flea extracts from three manufacturers (55), although only a few reacted to the extracts of all manufacturers. Delayed-type reactions after 24 and 48 h were observed in fewer cats, again not often uniformly reacting to the extracts of all manufacturers (55).…”
Section: Allergens In Feline Medicinementioning
confidence: 99%
“…Laffort et al [ 9 ] suggested that skin tests with pure flea saliva provided the best correlation between the clinical approach to FAD diagnosis and intradermal reactivity. In cats, Bond et al [ 13 ] compared the results of a serological test and intradermal reactivity with different commercially available C. felis antigens. A challenge with living fleas was used to assess the presence or absence of sensitization to C. felis .…”
Section: Discussionmentioning
confidence: 99%
“…A challenge with living fleas was used to assess the presence or absence of sensitization to C. felis . Considering this “gold standard”, Bond et al [ 13 ] were able to calculate the sensitivity of the serological test (0.88) and that of the intradermal tests (0–0.33).…”
Section: Discussionmentioning
confidence: 99%